2022
DOI: 10.17268/sci.agropecu.2022.007
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic extract of Crotalaria longirostrata: Identification of secondary metabolites and insecticidal effect

Abstract: The complications caused by the generation of resistance in the psyllid Bactericera cockerelli by chemical pesticides, raise the need for the alternative use of products that reduce resistance and ensure better control. The species Crotalaria longirostrata is a source of secondary metabolites, which show possible activity against insect pests. The objective of the research was to identify the compounds of the crude methanolic extract of C. longirostrata leaves, as well as to evaluate their biological activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Aqueous extracts of Posidonia oceanica revealed that phenolic compounds, glycosides, and terpenes played a crucial role in the development of the roots and leaves of S. lycopersicum and Cucumis sativus [22]. The methanolic extracts of C. longirostrata and A. mexicana used in this study contain secondary metabolites previously identified as significant components in these plants [23,24].…”
Section: Introductionmentioning
confidence: 61%
“…Aqueous extracts of Posidonia oceanica revealed that phenolic compounds, glycosides, and terpenes played a crucial role in the development of the roots and leaves of S. lycopersicum and Cucumis sativus [22]. The methanolic extracts of C. longirostrata and A. mexicana used in this study contain secondary metabolites previously identified as significant components in these plants [23,24].…”
Section: Introductionmentioning
confidence: 61%
“…PAs from plants are toxic compounds that can cause mutations in DNA in herbivores and humans . The identification of one alkaloid belonging to the iminosugar group was reported and related to Chipilin’s insecticidal action . The oxaspiro compound, reported as a diketone or akyl-ketone, has been detected by GC-MS in Brasiliorchis schunkeana and Ficus religiosa seeds. , Several activities such as steroidal antimineralocorticoid, antiandrogen, and glucocorticoid have been reported for this compound .…”
Section: Resultsmentioning
confidence: 99%
“…As a folk medicine, Chipilin extracts are used to treat several health conditions. ,, The antimicrobial, antifungal, insecticidal, and anticancer activities of acetonic and methanolic extracts of Chipilin leaves and branches have been reported. As an ethnomedicine, Chipilin is recommended as an evening meal to treat insomnia and anxiety. , However, its pharmacological activity as a sedative agent is not well-known; in addition, little is known about the compounds that are present in Chipilin extracts that could be related to this action. Thus, further research is needed. , On the other hand, the selection of an efficient extraction method is decisive for the identification of novel phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Hexanedioic acid, bis(2ethylhexyl) ester is one of the compounds illustrated by the GC-MS assay of the alcoholic extract of Lasiodiplodia pseudotheobromae, the extract showed antibacterial activities against both Grampositive and Gram-negative bacteria (23). The compound -Pyrimidine, 4,6-dimethoxy-5-nitro was among the compounds detected by GC-MS examination of the methanolic extract of Crotalaria longirostrata leaves, the extract showed activity against the nymph insect pest Bactericera cockerelli (31). Cycloheptasiloxane, tetracamethyl-showed antifungal activities (38) as well as antioxidant, antimicrobial and cytotoxic properties against a range of microbes (24).…”
Section: Effects Of Endophytic Fungal Filtrates On the Growth Of Some...mentioning
confidence: 96%